2003
DOI: 10.1021/ma034695a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Bonding Strength on the Microstructure and Crystallization Behavior of Crystalline Polymer Blends

Abstract: Combinations of differential scanning calorimetry, Fourier transform infrared spectroscopy, optical microscopy, and small-angle X-ray scattering were used to investigate the influence of hydrogen bonding strength on the crystallization kinetics and morphologies in poly(ε-caprolactone) (PCL) blends with three different well-known hydrogen bond donating polymers, i.e., phenolic, poly(vinylphenol) (PVPh), and phenoxy. The strength of the intercomponent interactions in the blend system depends on the hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 71 publications
(133 reference statements)
3
66
0
Order By: Relevance
“…The strength and extent of hydrogen bonding in copolymer or polymer blends depend on the respective affinities [4][5][6] of their hydrogen bond donors and acceptors. Polymer blend systems based on poly(vinyl phenol)/poly(4-vinyl pyridine) (PVPh/P4VP) and poly(vinyl phenol)/poly(vinyl pyrrolidone) (PVPh/PVP), which have been classified as strong hydrogen bonding systems (inter-association equilibrium constants (K A ) of 1200 and 6000, respectively), have been studied widely [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The strength and extent of hydrogen bonding in copolymer or polymer blends depend on the respective affinities [4][5][6] of their hydrogen bond donors and acceptors. Polymer blend systems based on poly(vinyl phenol)/poly(4-vinyl pyridine) (PVPh/P4VP) and poly(vinyl phenol)/poly(vinyl pyrrolidone) (PVPh/PVP), which have been classified as strong hydrogen bonding systems (inter-association equilibrium constants (K A ) of 1200 and 6000, respectively), have been studied widely [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Ullmann et al [4] showed that the lamellar thickness of poly(vinylidene fluoride) (PVDF) decreases with increasing concentration of poly(methyl methacrylate) (PMMA) in the blend. The radial growth rate of poly(ethylene oxide) (PEO) spherulites decreases and its half time of crystallization increases at a given crystallization temperature in the PEO/ PMMA and PEO/poly(vinyl acetate) (PVAc) blends.…”
Section: Introductionmentioning
confidence: 99%
“…These absorptions can be well fitted in the Gaussian function as shown in Figure 8 calculated by using an appropriate absorptivity ratio (a R ¼ a HB /a F ¼ 1.5) which has been discussed in our previous study. [27] The results from curve fitting are summarized in Table 3, indicating that the hydrogen bonded fraction of the carbonyl group increases with the PVPh content. In addition, the crystallinity of PCL decreases with the increase in the PVPh content.…”
Section: Ft-ir Analysesmentioning
confidence: 99%